Dose-compatible grating-based phase-contrast mammography on mastectomy specimens using a compact synchrotron source. Issue 1 (December 2018) - Eggl, Elena; Grandl, Susanne; Sztrόkay-Gaul, Anikό; Dierolf, Martin; Jud, Christoph; Heck, Lisa; Burger, Karin; Günther, Benedikt; Achterhold, Klaus; Mayr, Doris; Wilkens, Jan; Auweter, Sigrid; et al.
Abstract With the introduction of screening mammography, the mortality rate of breast cancer has been reduced throughout the last decades. However, many women undergo unnecessary subsequent examinations due to inconclusive diagnoses from mammography. Two pathways appear especially promising to reduce the number of false-positive diagnoses. In a clinical study, mammography using synchrotron radiation was able to clarify the diagnosis in the majority of inconclusive cases. The second highly valued approach focuses on the application of phase-sensitive techniques such as grating-based phase-contrast and dark-field imaging. Feasibility studies have demonstrated a promising enhancement of diagnostic content, but suffer from dose concerns. Here we present dose-compatible grating-based phase-contrast and dark-field images as well as conventional absorption images acquired with monochromatic x-rays from a compact synchrotron source based on inverse Compton scattering. Images of freshly dissected mastectomy specimens show improved diagnostic content overex-vivo clinical mammography images at lower or equal dose. We demonstrate increased contrast-to-noise ratio for monochromatic over clinical images for a well-defined phantom. Compact synchrotron sources could potentially serve as a clinical second level examination.